Pengaruh Strategi Pemanfaatan Media Sosial untuk Meningkatkan Pemasaran Produk UMKM Sekar Handycraft - Agung Triayudi; Syafrida Hafni Sahir; Mesran; Suginam (JPM: Jurnal Pengabdian Masyarakat, 2023)
Understanding the impact of social media utilization strategies that can attract consumer attention in order to increase product marketing is essential. Social media brings various benefits in a business context, such as increasing business exposure, expanding target market reach, building public interest and brand awareness, and providing a tool to measure the success of marketing campaigns. Sekar Handycraft SME are currently not optimizing the use of social media due to limited understanding of attracting consumer attention, which is the main cause. Therefore, to increase the competence of the Sekar Handycraft team, it is necessary to organize workshops or training to deepen understanding of the effects of using social media strategies in increasing product promotion. Through community service efforts at SME Sekar Handycraft, it is hoped that knowledge about social media utilization strategies can become a valuable asset for the SME Sekar Handycraft team so that they can more efficiently use social media to intensify product marketing.